(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The issue of women’s empowerment is a preoccupation for many specialists in the field of women’s development, and many studies, whether at the international or local level, have tried to identify the important roles occupied by women and the repercussions that women are affected by due to the crises that afflict the economies of countries on the one hand, and society in all its categories from On the other hand . And since the empowerment of women and ways to advance them economically, are among the most prominent strategic issues that see women as an essential element in the development process and the progress of society, given the challenges faced by Iraqi women over the decades and the multiplicity and widening of qualitative gaps, the National Policy for the Empowerment of Iraqi Women 2021 came to advocate the empowerment of women It affirms its pioneering role in the development process, declaring that the contents of this policy reflect the process of change in the culture of discrimination and building a culture of equality and equality in all its value, psychological and legal dimensions and increasing its participation in state authorities and decision-making.